Analisis Hubungan Komitmen Kerja terhadap Produktivitas Kerja Staf Universitas Nahdlatul Ulama Sumatera Utara (UNUSU) - Zon Saroha Ritonga (Medan Resource Center, 2022)
This study aims to reveal how the relationship between work commitment and productivity of staff at the Nahdlatul Ulama University of North Sumatra (UNUSU). The method used in this study is a qualitative research approach. Validation of research data was carried out using triangulation techniques through observation, interviews and document studies. The results of this study revealed four findings, namely: (1) University leaders have made standard operating procedures for each staff work unit so that it is easier to work and there is a clear career path for each employee. (2) The work productivity of UNUSU staff has increased, the Chancellor continues to improve the quality of education on the campus. (3) Efforts to increase staff commitment have encountered several obstacles, the Chancellor has tried to carry out his managerial functions, one of which is making plans to increase employee commitment to the maximum extent possible, but the obstacle is budget constraints so that the programs that have been prepared have not been implemented optimally. (4) The work commitment of Unusu staff is high because the majority of staff are Nahdlatul Ulama residents so they think that working at NU tertiary institutions does not only expect a salary but also participates in growing the Nahdlatul Ulama organization. The conclusions of this study are: The dominant organizational commitment of UNUSU staff is continuity commitment, followed by affective and normative commitment. Referring to the general condition that is classified as having high commitment, this finding shows that in general the staff will feel a loss if they leave the workplace, this has an impact on the work productivity of the staff.